Does Race Matter for Police Use of Force? Evidence from 911 Calls - Hoekstra, Mark; Sloan, CarlyWill (American Economic Review, 2022)
This paper examines race and police use of force using data on 1.6 million 911 calls in two cities, neither of which allows for discretion in officer dispatch. Results indicate White officers increase force much more than minority officers when dispatched to more minority neighborhoods. Estimates indicate Black (Hispanic) civilians are 55 (75) percent more likely to experience any force, and five times as likely to experience a police shooting, compared to if White officers scaled up force similarly to minority officers. Additionally, 14 percent of White officers use excess force in Black neighborhoods relative to our statistical benchmark. (JEL H76, J15, K42, R23)